104k views
2 votes
Subtract b (b²+b -7) + 5 from 3b² – 8 and find the value of expression obtained for b = -3. please explain how you got the answer

1 Answer

4 votes

Answer:

16

Explanation:

Subtracting the 2 expressions

3b² - 8 - b(b² + b - 7) ← distribute parenthesis

= 3b² - 8 - (b³ + b² - 7b) ← distribute parenthesis by - 1

= 3b² - 8 - b³ - b² + 7b ← collect like terms

= - b³ + 2b² + 7b - 8 ← substitute b = - 3 into the expression

= - (- 3)³ + 2(- 3)² + 7(- 3) - 8

= - (- 27) + 2(9) - 21 - 8

= 27 + 18 - 21 - 8

= 16

User Arye Rosenstein
by
6.6k points